PENINGKATAN PERCAYA DIRI SISWA DALAM BELAJAR MELALUI LAYANAN KONSELING KELOMPOK - Desi Ardianti; Giyono Giyono; Yusmansyah Yusmansyah (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this is increase the confidence of students in learning through group counseling services.The problem in this research is self-confidence of students were low. The method used in this study is an experimental method to design One-Group Pretest-Posttest. Data collection techniques in this study using observation and interviews The results as shown from the results of data analysis using the sign test or t-test of pretest and posttest results thitung= 11,31 ttabel = 1,896 then, Ho is rejected and Ha accepted.Advice that can be given is (1) The guidance and counseling teacher should be able to improving students confidence by using group counseling services (2) To the researchers, should be able to do research on the different subjects with conditions using the same service and other services 3) The other researchers to use group counseling services for different research problems. Keyword : self-confidence, Learning, group counseling services